ENVIRONMENTAL PROBLEMS AS A FACTOR IN THE DEVELOPMENT OF DISEASES AMONG THE POPULATION (Eureka Journal of Physical and Chemical Research, 2026)
Environmental factors play a key role in shaping human health. This article examines the main types of environmental pollution (air, water, soil), as well as their impact on the development of various diseases. The mechanisms by which toxicants affect the body, including the respiratory, cardiovascular, endocrine, and immune systems, are analyzed. Environmental risks are shown to be a significant factor in the increase in chronic and infectious diseases.
Keywords: Ecology, pollution, health, toxicants, diseases, environment.